The Nisbah of Indomaret Musyarakah Franchise in Indonesia: MUI Approach - Fauzi, Inna (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2022)
Abstract: The retail industry is an Indonesian business that provides basic needs and daily needs. This industry is engaged in a promising trading business. Conducting joint ventures with the public and business entities who wish to open a business in the field of trade (business retail) with a franchise system. On the other hand, the concept of cooperation promoted by the DSN MUI fatwa No. 08/DSN-MUI/IV/2000 must also continue to be applied for the realization of the Musyarakah concept. The purpose of this study was to find out how the calculation of the musharaka ratio of retail products at Indomaret in Kudus and how to analyze the fatwa of DSN MUI No 08/DSN-MUI/IV/2000 on the implementation system of calculating the musharaka ratio of retail products at Indomaret in Kudus. This study uses a qualitative descriptive method with a juridical-empirical approach. The results showed that the calculation of the musharaka ratio for retail products at Indomaret in Kudus was not in accordance with Islamic law through the fatwa of DSN MUI No 08/DSN-MUI/IV/2000 on the principle of Distribution of Business Results. In addition, the implementation system for calculating the musharaka ratio for retail products at Indomaret in Kudus tends to be subjective, not as in the Qur'an letter an-Nahl:9.Abstrak: Industri ritel merupakan bisni Indonesia yang menyediakan kebutuhan pokok dan kebutuhan sehari-hari. Industri ini bergerak dalam bidang usaha perdagangan yang cukup menjanjikan Mengadakan kerja sama (joint venture) dengan masyarakat dan badan usaha yang ingin membuka usaha dalam bidang perdagangan (businessretail) dengan sistem waralaba. D isisi lain, konsep kerja sama yang diusung oleh fatwa DSN MUI No 08/DSN-MUI/IV/2000 juga harus berus diterapkan demi terwujudnya konsep Musyarakah. Tujuan penelitian ini adalah untuk mengetahui bagaimana pelaksanaan perhitungan nisbah musyarakah produk retail pada Indomaret di Kudus serta bagaimana analisa fatwa DSN MUI No 08/DSN-MUI/IV/2000 terhadap sistem pelaksanaan perhitungan nisbah musyarakah produk retail pada Indomaret di Kudus. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan yuridis-empiris. Hasil penelitian menunjukkan bahwa pelaksanaan perhitungan nisbah musyarakah produk retail pada Indomaret di Kudus tidak sesuai dengan Hukum Islam melalui fatwa DSN MUI No 08/DSN-MUI/IV/2000 tentang prinsip Distribusi Hasil Usaha. Selain itu, sistem pelaksanaan perhitungan nisbah musyarakah produk retail pada Indomaret di Kudus cenderung bersifat subjektif tidak sebagaimana dalam al-Qur’an surat an-Nahl ayat 9.